Fatigue failure analysis using the theory of critical distance - Ruslizam, Daud; Ahmad Kamal, Ariffin; Shahrum, Abdullah; A. Emran, Ismail (Trans Tech Publications, 2011)
Link to publisher's homepage at http://www.scientific.net/